2019
DOI: 10.1177/1040638719863102
|View full text |Cite
|
Sign up to set email alerts
|

Canine circoviral hemorrhagic enteritis in a dog in Connecticut

Abstract: A 5-mo-old Bassett Hound–Labrador Retriever cross was autopsied following a bout of lethargy, inappetence, and bleeding gums. Mucous membranes were white, and the small intestine was blue-black; the colon contained black feces. The spleen was swollen, and multiple lymph nodes were enlarged and hemorrhagic. Microscopically, the small intestine had focal crypt cell necrosis and circumferential transmural vasculitis, the latter the cause of infarction and the blue-black coloration. Lymphocytes were necrotic in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
12
0
7
Order By: Relevance
“…The relationship between ElkCV and the lesions in this case remains unclear. In dogs, there has been a proposed association between hemorrhagic gastroenteritis with vasculitis and canine circovirus 36 ; however, a case-control study also identified the virus in healthy control dogs, suggesting that infection is widespread 37 . Similarly, PCV1 is not known to cause disease in pigs and many pigs infected with PCV2 do not develop severe lesions.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between ElkCV and the lesions in this case remains unclear. In dogs, there has been a proposed association between hemorrhagic gastroenteritis with vasculitis and canine circovirus 36 ; however, a case-control study also identified the virus in healthy control dogs, suggesting that infection is widespread 37 . Similarly, PCV1 is not known to cause disease in pigs and many pigs infected with PCV2 do not develop severe lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, CanineCV was identified in Italy and was thought to be the causative agent of canine necrotizing vasculitis and lymph node granuloma, which can cause vomiting and hemorrhagic diarrhea in dogs [ 2 , 3 ]. To date, CanineCV has been reported in several countries, indicating that the virus has spread worldwide [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The genome of CanineCV is approximately 2063–2064 nt in size and primarily contains three open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest that CanineCV might cause haemorrhagic diarrhoea in dogs. By PCR, CanineCV has been detected in the feces from 14 of 204 healthy dogs (6.9%) and 19 of 168 dogs with diarrhea (11.3%) 2 , and also, this agent has been detected in sporadic cases of dogs with vasculitis, histiocytic inflammation, or a combination 11 , 12 . On the other hand, the virus has been already reported in different wildlife carnivorous from Europe, mainly in Wolves ( Canis lupus ), red foxes ( Vulpes vulpes ) and virus from those wild animals share a genome identity up to 80%, suggesting that wildlife and dogs can interchange related circoviruses and that CanineCV could possibly be transmitted from dogs to wild canids, or vice versa 13 16 .…”
Section: Introductionmentioning
confidence: 99%